Features of the functioning of the hypothalamic-pituitary-thyroid axis in mice with Lewis carcinoma on the background of induced hyperthyroidism - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; I. V. Neskubina; E. I. Surikova; A. I. Shikhlyarova; L. K. Trepitaki; M. A. Gusareva; I. A. Udalenkova; E. O. Vasilieva; N. D. Cheryarina; V. V. Pozdnyakova (Исследования и практика в медицине)
Thyroid hormones (TH) influence the processes of cell proliferation and differentiation, but their role in the processes of carcinogenesis is contradictory.The purpose of the study. To study the effect of induced hyperthyroidism in mice of both sexes with intertwined Lewis carcinoma (LLC) on the activity of the hypothalamic-pituitary-thyroid axis (GGT).Materials and methods. The experimental model was mixed-sex mice of the C57BL/6 line with subcutaneously transplanted LLC on the background of induced hyperthyroidism (main group). Two control groups were used: control group I – mice with sodium liothyronine- induced hyperthyroidism and control group II – mice with subcutaneously transplanted LLC. On the 25th day after tumor transplantation, the level of thyrotropin- releasing hormone (TRH), thyroid- stimulating hormone (TSH), triiodothyronine (T3), total and free thyroxine (T4, FT4) was determined in the homogenates of GGT organs and in blood serum.Results. In female mice, hyperthyroidism caused an increase in the level of TRH in the hypothalamus and a decrease in TSH in the pituitary gland; in males, a decrease in TRH only in the hypothalamus. In control group II, euthyroid disorder syndrome developed: In mice of both sexes, serum levels of T4 and FT4 were found to decrease against the background of unchanged T3 levels and an increase in TSH content only in females. In the females of the main group, an increase in the level of TSH in the thyroid gland caused a decrease in T3 content in 73 % of animals against the background of normal T4 and elevated FT4 levels, in 27 % of females the T3 level increased. In males, in 73 % of the observations, the T3 level was increased against the background of high T4 and FT4 values and unchanged TSH levels. In the skin and LLC samples of the mice of the main group, an increase in T3 levels was noted.Conclusion. The growth of LLC against the background of hyperthyroidism is a process with multifactorial effects. High levels of T3 in blood serum and skin stimulated the proliferation of tumor cells, which led to the formation of subcutaneous tumors of a larger volume in the mice of the main group. Sex differences in the GGT response indicate different mechanisms that implement pathological processes.